Cochlear Implantation in Patients With Superficial Siderosis. Issue 7 (August 2015) - Modest, Mara C.; Carlson, Matthew L.; Wanna, George B.; Driscoll, Colin L.
<x xml:space="preserve">Abstract</x> Objective To date, there have been less than 30 cases of cochlear implantation (CI) in patients with superficial siderosis (SS) reported in the literature. The primary objective of the current study is to evaluate CI outcomes in six additional patients (seven ears) with SS and sensorineural hearing loss (SNHL) and to perform a systematic review of the literature. Study Design Case series and systematic review of the literature. Setting Two tertiary academic CI centers. Patients All patients with SS who underwent CI between 2007 and 2014. Intervention(s) Cochlear implantation. Main Outcome Measures Pre- and post-implantation speech perception scores and durability of benefit. Results A total of seven ears (four males; median age 52 yr) with SS and SNHL met inclusion criteria. All patients developed progressive bilateral SNHL that was no longer amenable to conventional hearing aids. Additional presenting symptoms included vestibulopathy (n = 4), cerebellar ataxia (n = 3), mild dementia (n = 1), and myelopathy (n = 1). All patients underwent uncomplicated CI, and intraoperative device telemetry revealed normal responses in all electrodes. The median postoperative auditory threshold average was 32.5 dB HL (range 16–36 dB) and the median postoperative CNC word score was 51% (range 46–64%). The median duration of follow-up was 15.5 months (range 3–64 mo). All patients demonstrated initial improvement in speech perception testing. Two patients had performance decline and worsening dementia resulting from progressive SS. Conclusion Cochlear implantation is a viable strategy for auditory rehabilitation in patients with SS and associated SNHL. Most individuals enjoy benefit from CI; however, patients should be counseled regarding the risks of performance decline with progressive SS.